2021
DOI: 10.3390/biom11040501
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Location of Protein Sites Binding Self-Associated Congo Red Molecules with Intercalated Drugs as Compact Ligands—Theoretical Studies

Abstract: In the search for new carriers capable of transporting toxic drugs to a target, particular attention has been devoted to supramolecular systems with a ribbon-like micellar structure of which Congo red is an example. A special promise of the possible use of such systems for directing drugs to a target emerges from their particular affinity to immune complexes and as an independent property, binding many organic compounds including drugs by intercalation. Serum albumin also appeared able to bind micellar particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Additionally, theoretical analyses showed that CR-Dox complexes are bound by BSA. Albumin is negatively charged, but inside the large cleft, it has short basic helices responsible for binding the negatively charged CR and the CR-Dox complex [28]. The results obtained in this study confirm the binding of the model drug (Dox) to CR and the formation of a large complex binding to albumin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, theoretical analyses showed that CR-Dox complexes are bound by BSA. Albumin is negatively charged, but inside the large cleft, it has short basic helices responsible for binding the negatively charged CR and the CR-Dox complex [28]. The results obtained in this study confirm the binding of the model drug (Dox) to CR and the formation of a large complex binding to albumin.…”
Section: Discussionsupporting
confidence: 75%
“…Ribbon-like supramolecular systems (SRLS), of which the representative is Congo red, are an example of such systems. Congo red type self-assembled ribbon-like structures (SRLS) were previously shown to interact with some proteins, including albumin [27][28][29]. CR also binds Dox by intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that planar DOX molecules can be incorporated into CR aggregates by intercalating the anthraquinone part between CR molecules [ 25 , 26 ]. What is more, CR has the ability to selectively bind to immune complexes and proteins [ 27 , 28 ]. This feature can be used to load supramolecular DOX/CR complexes on drug-carrying proteins, e.g., albumin [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%